2007
DOI: 10.1007/s11145-007-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between home literacy practices and developmental trajectories of emergent literacy and conventional literacy skills for Korean children

Abstract: Previous studies with English-speaking families in the North American context demonstrated that home literacy practices have positive influences on children's literacy acquisition. The present study expands previous studies by examining how home literacy practices are related to growth trajectories of emergent literacy skills (i.e., vocabulary, letter-name knowledge, and phonological awareness) and conventional literacy skills (i.e., word reading, pseudoword reading, and spelling), and by using data from Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 46 publications
6
68
0
11
Order By: Relevance
“…We also found that storybook exposure had an impact on child reading/spelling skills, which was not originally predicted by Senechal and Lefevre (2002) but is reported in previous research (Bus et al, 1995; Kim, 2009). Notwithstanding this, we found that the relationship between the informal home literacy environment and child language and literacy was largely explained by variance that was shared with maternal skills, consistent with Van Bergen et al (2016).…”
Section: Discussionsupporting
confidence: 68%
“…We also found that storybook exposure had an impact on child reading/spelling skills, which was not originally predicted by Senechal and Lefevre (2002) but is reported in previous research (Bus et al, 1995; Kim, 2009). Notwithstanding this, we found that the relationship between the informal home literacy environment and child language and literacy was largely explained by variance that was shared with maternal skills, consistent with Van Bergen et al (2016).…”
Section: Discussionsupporting
confidence: 68%
“…The acquisition of written language continuously improved with new skills, as the individual grows and it is totally dependent of the interactions with the environment (Finkbeiner and Coltheart 2009) that provides stimuli and experiences that are essential for this development as a primary means of social interaction (Kim 2009;Peeters et al 2009). Low SES children are more likely to reside in an environment that exhibits sharply lower attainment levels and, in addition, that repeatedly manifests higher rates of crime, divorce, unemployment, and population density than high SES children.…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrated a significant positive correlation between phonological skills in first language and the same skills in the second language, in addition of significant positive correlation between phonological skills in Hebrew and text reading and pseudo-word reading in English. Identical findings were revealed between Korean, considered as an alphabetic language, and English (Chiappe, Glaeser, & Ferko, 2007;Kim, 2009;Kang, 2012;McBride-Chang et al, 2005;Wang, Cheng, & Chen, 2006). According to these studies, there is cross-linguistic transfer of phonological awareness in spite of the differences in phonological representation between the two languages.…”
Section: Phonological Awarenessmentioning
confidence: 79%
“…According to these studies, there is cross-linguistic transfer of phonological awareness in spite of the differences in phonological representation between the two languages. For example, Kim (2009) found that identifying rhymes in Korean L1 correlated with phonological awareness in English L2. In addition, phonological skills in Korean positively contributed to the decoding of words in English, in spite of the difference in phonological representation between the two languages.…”
Section: Phonological Awarenessmentioning
confidence: 99%